Development of Physics Teaching Material: Guided Discovery Learning with Liveworksheet to Improve Work and Energy Problem Solving - Ellianawati, Ellianawati; Rahayu, Tri (STKIP Singkawang, 2024)
This study aims to describe the characteristics of teaching material, identify the level of feasibility, and determine the level of readability of teaching material based on guided discovery learning assisted by liveworksheet applications to improve problem-solving ability in work and energy material. The research method used is research and development with the ADDIE research design developed by Mollenda and Reiser in 2003 consisting of 5 stages, namely: 1) analyze; 2) design; 3) develop; 4) implement; and 5) evaluate. In this study only up to the develop stage. The feasibility test data collection used a questionnaire sheet with a Likert scale, while the readability test used the overlap test. The subjects of this research include physics lecturers, physics teachers, and students totaling 36. The characteristics of the teaching material developed contain work and energy material in the form of interactive pdfs equipped with discussion activities and experiments assisted by liveworksheet applications, sample problems and discussions, and evaluations with Polya problem-solving ability indicators. The results of the feasibility test of the teaching material obtained a score of 88%, indicating that it included very feasible criteria. The readability test obtained a result of 76.67%, so it is included in the criteria for teaching material that is easily understood by students. The results of this research can be utilized by teachers to teach the topic of work and energy, as well as to design and develop other learning materials that are more effective and interactive.